A Ka band microstrip to waveguide transition using a quasi‐triangle probe. Issue 8 (15th May 2017) - Li, Lei; Li, Jianxing; Wei, Xiaoyong; Zhang, Anxue; Ma, Hanqing
Abstract: In this article, a new Ka band microstrip to waveguide transition with combination of electric and magnetic coupling is introduced by using a quasi‐triangle structure. Consequently, the length of the proposed transition has been significantly diminished. A back‐to‐back prototype was fabricated based on the optimized dimensions to validate the design concept. The measured and simulated results are in a good alignment. The experimental results show that the return loss is better than 14.8 dB across the frequency range of 32‐40 GHz with an insertion loss of lower than 0.9 dB. The conversion efficiency for the single transition, therefore, is larger than 90.5%. Because of its broad operation bandwidth, low insertion loss, and compact size, the proposed embedded transition could find wide applications in most modern miniaturized MMIC devices and systems.